UC-Secure Dynamic Searchable Symmetric Encryption Scheme - Kurosawa, Kaoru; Sasaki, Keisuke; Ohta, Kiyohiko; Yoneyama, Kazuki (Advances in Information and Computer Security, 2016)
In a dynamic searchable symmetric encryption (SSE) scheme, a client can add/modify/delete encrypted files. In this paper, we first prove a weak equivalence between the UC security and the stand alone security based on the previous work on static SSE schemes. We next show a more efficient UC secure dynamic SSE scheme than before by replacing the RSA accumulator with XOR-MAC to authenticate the index table.